Validating a Livelihood Asset Scale in Lao PDR. Issue 4 (November 2014) - Durham, Jo; Fielding, Angela; Hoy, Damian; White, Rob
Mixed method designs are often used in scale development to generate potential items and enhance face validity. Less frequently, mixed method designs are used to examine other aspects of validity. As part of a larger evaluation in the Lao People's Democratic Republic, we developed a scale to assess household self-reported changes in access to livelihood assets following a mine action program. In this article, we detail the process of assessing measurement validity using mixed methods. The qualitative method of evaluation was based on an analysis of in-depth interviews with key informants. The quantitative evaluation relied on data collected from the scale administration ( N = 271) evaluated using Rasch measurement. The article offers an example to researchers interested in using mixed methods to assess validity in measurement development. It contributes to the growing literature on using mixed method designs to evaluate the properties of scales and to the methodological work on the measurement of access to livelihood assets.